Study of trapezoidal flexible horizontal piezoelectric cantilever beam based on ANSYS - Ahmad Syafiq, Deraman; M. H., Hasbullah; Niirmel, Ranjanendran; Mujahid, Mohamad (Springer Science and Business Media Deutschland GmbH, 2022)
This paper presents the analysis of energy harvester by utilizing trapezoidal adaptable piezoelectric cantilever beam in which applied on ocean wave. The limitation of blade configuration is it just spotlight on single design progression of ocean wave movement. The limited component model is built by utilizing ANSYS to enhance the blade configuration to boost the output power. The analysis of trapezoidal adaptable piezoelectric plan shows the capacity to produce variable of electric force from least 18.4 µW up to 146.80 µW, with measurement of width, length, tallness of piezo is 5 mm, 30 mm, 0.10 mm and abundancy of ocean wave surface of 1.5 m individually.